PENYULUHAN LITERASI MEDIA DAN ETIKA DIGITAL BAGI MAHASISWA MELALUI PELATIHAN DARING INTERAKTIF - Yati Bt Samsuddin; Andry Priyadharmadi Purnama; Buya Hamka; Nurjayanti Nurjayanti (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
The high level of digital media usage among university students is not always accompanied by sufficient media literacy or awareness of digital ethics. Many students engage in sharing unverified information, using inappropriate language on social media, and demonstrating limited understanding of privacy and copyright principles. To address these issues, a community service activity was conducted in the form of an interactive online workshop titled